A comparison of the efficacy of once-daily fluticasone furoate/vilanterole with twice-daily fluticasone propionate/salmeterol in asthma-COPD overlap syndrome. (December 2015) - Ishiura, Yoshihisa; Fujimura, Masaki; Shiba, Yasutaka; Ohkura, Noriyuki; Hara, Johsuke; Kasahara, Kazuo
Abstract: Background: Asthma-chronic obstructive pulmonary disease overlap syndrome (ACOS) is important because patients with ACOS have significantly worse outcomes compared with those with asthma or chronic obstructive pulmonary disease (COPD) alone. Inhaled corticosteroids (ICS), together with a long-acting β2 agonist (LABA), are recommended, but no therapeutic studies for ACOS have been conducted. Recently, fluticasone furoate/vilanterole (FF/VI) has been approved as the first once-daily ICS/LABA combination therapy for asthma and COPD. Methods: A 12-week, randomized, open-label cross-over study was conducted in 16 patients with ACOS to compare the effectiveness of once-daily FF/VI 200/25 μg vs. twice-daily fluticasone propionate/salmeterol (FP/SAL) 500/50 μg. The study period included a 4-week run-in, the first 4-week treatment, and the second 4-week treatment. Respiratory functions, including forced expiratory volume in 1 s (FEV1 ) and respiratory impedance using the forced oscillation technique (FOT), were measured, as was fractional exhaled nitric oxide (FeNO). A COPD assessment test (CAT) scores and asthma control test (ACT) scores were recorded 0, 4, and 8 weeks after randomization. Results: The mean values for the FEV1 were 1.33 (±0.29) L in the run-in period, 1.38 (±0.39) L after the FP/SAL treatment period, and 1.47 (±0.38) L after the FF/VI treatment period. The FEV1 value after the FF/VI treatment was significantly greater than the value after the run-in period (p < 0.01). FOT parameters, FeNO levels, CAT scores, ACT scores, and other blood tests were not significantly different during the run-in period, the FP/SAL treatment period, and the FF/VI treatment period. Conclusions: FF/VI, the first once-daily ICS/LABA, can provide substantial improvement in lung functions, indicating that FF/VI should be considered for the regular treatment of ACOS.